Risk Assessment of Injury to Palmar Cutaneous Branch of the Median Nerve Using High-Resolution Ultrasound - Young Ha Jeong; Jun Ho Choi; Hyuk Sung Choi; Seok Kang; Seung Nam Yang; Joon Shik Yoon (Annals of Rehabilitation Medicine, 2019)
Objective To evaluate the relationship between the palmar cutaneous branch of median nerve (PCBMN) and surrounding anatomical structures by using high-resolution ultrasound (HRUS) to assess the risk of PCBMN injury. Methods The PCBMN course and the characteristics of bilateral distal forearms and wrists of 30 healthy volunteers were identified. The distance between PCBMN and other anatomical structures at three different levels along its course were measured using HRUS. Moreover, the depth of PCBMN from skin and its cross-sectional area (CSA) were measured. Results HRUS showed the PCBMN in all subjects. PCBMN branched off from the radial aspect of the median nerve (MN) at 4.69±0.89 cm proximal to the bistyloid line (BSL) and extended radially toward the flexor carpi radialis (FCR) tendon. PCBMN was within the ulnar edge of FCR tendon sheath, and became more superficial and perforated the antebrachial fascia between the FCR tendon laterally and the palmaris longus (PL) tendon medially. PCBMN was located at 4.08±0.72 mm on the ulnar aspect of the FCR tendon and 4.78±0.36 mm radially on the PL tendon at BSL. At the distal wrist crease level, the PCBMN was located at 5.68±0.58 mm on the ulnar side of the FCR tendon. The PCBMN depth from skin at BSL and its branching point was 1.92±0.41 and 7.95±0.79 mm, respectively. The PCBMN CSA was 0.26±0.15 mm2 at BSL. Conclusion HRUS can be used to identify PCBMN and its relationship with other anatomical structures. Our data can be used to predict PCBMN location, and prevent complications associated with invasive procedures involving the wrist.